Dermatophytosis in companion animals: A review - Paryuni, Alsi Dara (Vet World, 2020)
Dermatophytosis, a zoonotic disease, is caused by fungi of three main genera, namely, Micropsorum, Trichophyton, and Epidermophyton. Specific lesions of dermatophyte infections are localized in the face, legs, and/or tail. Skin lesions in infected animals demonstrate localized alopecia, erythema, and crust, which are more commonly known as ringworm. Factors that affect dermatophytosis include the dermatophyte species; virulence factors of the agent; and the immune status, age, and sex of the host. High levels of cortisol and pro-inflammatory cytokines have also been reported to play an important role in dermatophyte infection. This review aims to explore and understand factors that affect dermatophyte infection with an emphasis on the prevalence, clinical signs, pathogenesis, immune response, and the roles of cortisol and cytokines in companion animals infected by a dermatophyte.